2021
DOI: 10.1108/afr-09-2020-0149
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between agricultural production and agricultural loans for banking sector groups in Turkey

Abstract: PurposeThis study aims to determine the nexus between agricultural production and agricultural loans for the period Q1 2003–Q4 2018 in Turkey.Design/methodology/approachThe authors employ the time-series analyses within the scope of the study. Firstly, they run the Engle–Granger two-step cointegration test and the Toda–Yamamoto causality analysis. They also use the dynamic ordinary least squares (DOLS) model estimator and estimate the vector autoregression model for predicting the dynamic structure of time ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…The current finding, cointegrating relationship between agricultural credit disbursements on cereal yield in Odisha, is a novel contribution to the agricultural credit and agricultural yield literature. A similar result is also previously evidenced in the studies of Osabohien et al (2019) and Osabohien, Adeleye et al (2020) for Nigeria, Kaya and Kadanalı (2021) for Turkey, Chandio et al (2021) for Pakistan and so on. The probable reasons for such findings are; first, providing agricultural loans can be seen as an investment in farming, leading to higher productivity and, in the end, higher yields (Chandio et al, 2018).…”
Section: Cointegration-bounding F-testsupporting
confidence: 88%
See 2 more Smart Citations
“…The current finding, cointegrating relationship between agricultural credit disbursements on cereal yield in Odisha, is a novel contribution to the agricultural credit and agricultural yield literature. A similar result is also previously evidenced in the studies of Osabohien et al (2019) and Osabohien, Adeleye et al (2020) for Nigeria, Kaya and Kadanalı (2021) for Turkey, Chandio et al (2021) for Pakistan and so on. The probable reasons for such findings are; first, providing agricultural loans can be seen as an investment in farming, leading to higher productivity and, in the end, higher yields (Chandio et al, 2018).…”
Section: Cointegration-bounding F-testsupporting
confidence: 88%
“…Though the findings of the above literature provide few insights on the impact of agricultural credit disbursement on agricultural yields, several shortcomings can be realized from the past studies. For instance, from the global perspective, several recent studies have reported the impact of agricultural credit on agricultural yields (Agbodji and Johnson, 2021;Chandio et al, 2021;Diallo et al, 2020;Kaya & Kadanalı, 2021;Miah et al, 2006;Osabohien et al, 2019;Wicaksono, 2014). However, any unarguable decision cannot be generalized to Odisha because country-specific attributes play a crucial role in the respective agricultural sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing production levels requires either government intervention or investment policies (Babu & Akramov, 2022;Jayne et al, 2010). Such investment and policies must invite the private sector to maximize their investment, output, and social impact (Kaya & Kadanalı, 2021;Kumar et al, 2017). Private actors, including financial institutions and commercial banks, should consider offering agricultural credit to the larger-scale production farms and the smallholder farms in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Recent tentative studies in Africa have been limited only to agricultural finance policies and recommendations (Sikandar et al, 2021). One study done in turkey found that agriculture loans and deposits positively impact agriculture production (Kaya & Kadanalı, 2021). Likewise, Nigeria discovered the same effects (Asaleye et al, 2020).…”
Section: Introductionmentioning
confidence: 99%